Alternative to General Anesthesia for a Stat Cesarean Delivery in a Patient with a Large Arteriovenous Malformation Involving the Cervicomedullary Junction in Active Labor - Christiano dos Santos e Santos; David A. Joyner; Cristiane A. Tuma Santos; Bernadette E. Grayson; Arthur Calimaran; Douglas R. Bacon (Case Reports in Anesthesiology)
A 20-year-old G1P0 patient at 38 weeks and 1 day of gestation was admitted for emergency cesarean delivery. Her past medical history was positive for cervicomedullary arteriovenous malformation (AVM) that ruptured three years before. Spontaneous vaginal delivery was contraindicated by neurosurgery. Aiming for cardiovascular stability and immediate reduction of sympathetic activity, a combined spinal epidural was successfully placed. An uneventful cesarean section was performed. The patient was transferred to the intensive care unit neurologically intact and discharged home after 8 days. This report describes an unusual anesthetic management of a patient with a large AVM in active labor.